Diffuse attenuation coefficient retrieval in CDOM dominated inland water with high chlorophyll-a concentrations - Gomes, Ana Carolina Campos [UNESP]; Bernardo, Nariane [UNESP]; do Carmo, Alisson Coelho [UNESP]; Rodrigues, Thanan; Alcântara, Enner [UNESP] (MDPI, 2018)
The kd(490) is a vertical light attenuation coefficient and an important parameter for water quality. The kd estimates are often based on empirical and semi-analytical algorithms, designed for oceanic and coastal waters. However, there is a lack of information about the performances of these models to inland waters dominated by chromophoric dissolved organic matter (CDOM). Therefore, to contribute to this investigation, nine empirical models based on the blue-to-green and blue-to-red ratios and chlorophyll-a (Chl-a) concentration were evaluated, as well as three semi-analytical models using bands from the Operational Land Imager (OLI)/Landsat-8. The errors (mean absolute percentage error, MAPE > 80%) presented by the empirical models confirmed that the blue-to-green ratio failed in retrieving kd(490) in an environment dominated by CDOM. Similar failures occurred with the models using the Chl-a concentration (MAPE ~60%) as input. A semi-analytical approach showed the lowest error (MAPE = 41.04%) in the estimate of the inherent optical properties for complex waters in order to reduce the errors above. After retrieval of kd(490) using the semi-analytical model, seasonal patterns were observed, and high values of kd(490) were detected in the dry season possibly due to the increase of the concentration of the optically-significant substances (OSS).
Keywords: Bio-optical models; Light attenuation; Satellite images; Water quality